Participatory development of an indigenous goat cheese product: monitoring of the chemical, nutritional and microbiological quality from milk to cheese - Habteyohannes, Efrem Ghebremeskel (University of the Free State, 2001)
The milk of indigenous goats has great potential in providing a nutritional food for poverty stricken communities. The aim of this study was to investigate the microbiological (spoilage and pathogenic), chemical (fat, protein and lactose) and nutritional (minerals, vitamins A and E) quality of indigenous goat milk from Mpumalanga and North West and compare it to Saanen goat milk. In almost all the quality parameters, the milk of the indigenous goats had a higher quality than the Saanen milk. The differences of most of the quality parameters between the indigenous and Saanen goat milk were ascribed to feed, breed, lactation stage, age, health status and the fact that the Saanen goats were machine-milked, while the indigenous goats were milked by hand. Another aim was to produce a Gouda-type cheese from each of the three goat milks. The microbiological (spoilage and pathogenic), chemical (moisture, total solids, ash, water activity, salt, fat content, free fat in dry matter, total free fatty acids, rancidity [TBA-value], fatty acid composition, protein content and proteolysis), nutritional (minerals and vitamins A and E) and sensory quality of the cheeses were then determined. The milk of the North West indigenous goats was acidic at the start of cheese production, but was normalized during production. The acidic nature of the cheese had, however, a negative effect on most of the quality parameters and resulted in a harder cheese with a goaty smell. The Mpumalanga and Saanen cheeses compared well in all the quality parameters and the sensory analysis suggested that no significant difference were present between these two cheeses. The conclusion was drawn that the milk of indigenous goats are an excellent way to provide a nutritional quality food, expand commercial markets, create jobs and increase income in rural areas.

Die melk van inheemse bokke het groot potensiaal vir die voorsiening van 'n voedsame voedsel vir arm gemeenskappe. Die doel van hierdie studie was om die mikrobiologiese (bederf en patogene), chemiese (vet, proteïen en laktose) en voedingswaarde (minerale, vitamiene A en D) kwaliteit van inheemse bokmelk vanaf Mpumalanga en Noord-Wes te ondersoek en dit met Saanen bokmelk te vergelyk. Die inheemse bokmelk het amper in al die kwaliteitsparameters In hoër kwaliteit as die Saanen melk gehad. Die verskille tussen die inheemse en Saanen bokmelk is toegeskryf aan faktore soos voedsel, ras, laktasie stadium, ouderdom, gesondheidstatus en die feit dat die Saanen bokke met melktoerusting gemelk is terwyl die inheemse bokke met die hand gemelk is. 'n Ander doelwit was om 'n Gouda-tipe kaas van elk van die drie bokmelke te vervaardig. Die mikrobiologiese (bederf en patogene), chemiese (vog, totale vastestowwe, as, wateraktiwiteit, sout, vetinhoud, vry vet in droë massa, totale vrye vetsure, galsterigheid [TBA-waarde l, vetsuur samestelling, proteïen inhoud en proteolise), voedingswaarde (minerale, vitamiene A en D) en sensoriese kwaliteit van die kase is daarna bepaal. Die melk van die Noord-Wes inheemse bokke was suur aan die begin van kaasvervaardiging, maar die suurheid is gedurende vervaardiging genormaliseer. Die suur aard van die kaas het egter 'n negatiewe effek op meeste van die kwaliteits parameters gehad en het In harder kaas met 'n bokagtige reuk tot gevolg gehad. Die Mpumalanga en Saanen kase het goed ooreengekom in al die kwaliteits parameters en die sensoriese analiese het aangedui dat geen beduidende verskil tussen die twee kase teenwoordig was nie. Die gevolgtrekking is gemaak dat melk van inheemse bokke In uitstekende produk is om 'n voedsel te voorsien wat hoë voedingswaarde het, wat gebruik kan word om kommersiële markte uit te brei, werk te verskaf en inkomste in landelike areas te verhoog.
Dissertation (M.Sc. (Food Microbiology))--University of the Free State, 2001
Keywords: Indigenous goats; Saanen goats; Milk; Cheese; Quality; Microbiological; Chemical; Nutritional; Sensory; Goat milk; Goat cheese; Dairy products -- Composition; Goat industry -- South Africa